2019
DOI: 10.1002/ejlt.201900040
|View full text |Cite
|
Sign up to set email alerts
|

Malondialdehyde, 4‐Hydroxy‐2‐Hexenal, and 4‐Hydroxy‐2‐Nonenal in Vegetable Oils: Formation Kinetics and Application as Oxidation Indicators

Abstract: The formation of three toxic reactive aldehydes, malondialdehyde (MDA), 4‐hydroxy‐hexenal (HHE), and 4‐hydroxy‐2‐nonenal (HNE), is investigated in five commonly consumed vegetable oils using a method based on the Schaal oven test. HHE is only detected in linseed oil (LO) and rapeseed oil (RO), while MDA and HNE are found to be present in all tested oils. The formation potential of MDA, HHE, and HNE in the tested oils is closely related to the initial polyunsaturated fatty acid (PUFA) content in the oil. Correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…It revealed that the concentration of various volatiles differed significantly between deteriorated and fresh samples, where unfriendly flavor ( e.g., aldehydes, olefins and alkanes) were higher in medium and serious deteriorated ones. Similar findings have been reported in a variety of foods ( Gayoso et al, 2017 , Ghorbani Gorji et al, 2019 , Ma et al, 2019 ). Moreover, as shown in Fig.…”
Section: Resultssupporting
confidence: 90%
“…It revealed that the concentration of various volatiles differed significantly between deteriorated and fresh samples, where unfriendly flavor ( e.g., aldehydes, olefins and alkanes) were higher in medium and serious deteriorated ones. Similar findings have been reported in a variety of foods ( Gayoso et al, 2017 , Ghorbani Gorji et al, 2019 , Ma et al, 2019 ). Moreover, as shown in Fig.…”
Section: Resultssupporting
confidence: 90%
“…The levels of 4-HHE and HNE reflect the proportion of omega-3 and omega-6 fatty acids in the oil (omega-3/omega-6 = 2.1) and in addition an increased autooxidation rate of the more unsaturated omega-3 fatty acids than the omega-6 fatty acids. However, another accelerated storage study of camelina oil kept at 60 °C for 30 days in air 44 , showed the same levels for HHE and HNE, i.e. about 0.6 µg/g oil.…”
Section: Discussionmentioning
confidence: 89%
“…The levels of 4-4-HHE and 4-HNE reflect the proportion of omega-3 and omega-6 fatty acids in the oil (omega-3/omega-6 = 2.1) and in addition an increased autoxidation rate of the more unsaturated omega-3 fatty acids than the omega-6 fatty acids. However, another accelerated storage study of camelina oil kept at 60 °C for 30 days in air 44 showed the same levels for 4-HHE and 4-HNE, i.e., about 0.6 μg/g of oil. This 4-HNE concentration corresponds to our 4-HNE concentration in CO after 6 weeks of storage at 40 °C, which is surprising, since the formation of hydroxyalkenals has been shown to be temperature-dependent, so higher levels would have been expected at higher temperatures.…”
Section: Discussionmentioning
confidence: 90%
“…In the present work, the formation of three toxically non‐volatile reactivate aldehydes, MDA, HHE and HNE, during deep‐frying of potato sticks and chicken breast meat in vegetable oils was investigated. Previously, we found that HHE/HNE could be used as alternative oxidation indicator to evaluate the peroxidation of vegetable oils, and proposed a simultaneous and competitive formation pathway of MDA, HHE and HNE (Ma et al , ). Considering the fact that French fries and fried chicken meat were the most consumed fried foods, potato sticks and chicken breast meat were chosen as the foodstuffs.…”
Section: Resultsmentioning
confidence: 99%
“…As typical α,β‐unsaturated aldehydes, HHE and HNE can be derived from the peroxidation of ω‐3 and ω‐6 PUFA, respectively. For this reason, it was recently demonstrated that HHE and HNE could be used as alternative indicators to depict the oxidation of ω‐3 and ω‐6 type oils characteristically (Ma et al , ). All these three aldehydes are highly reactive, indicating that they can undergo nucleophilic reactions with DNA, lipoproteins and peptides.…”
Section: Introductionmentioning
confidence: 99%